ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU DENGAN METODE ECONOMIC ORDER QUANTITY (EOQ) PADA USAHA MIE SINAR SULAWESI CAP DUA ANGSA GUNA PENINGKATAN EFISIENSI BIAYA PERSEDIAAN - Yogi Elsandi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2019)
Nowadays economy has developed very fast, along with the rapid development of science and technology which is increasingly modern makes the competition between companies become more intense. With the intense competition between companies encouraging each company to do a good inventory control in supporting and expediting the production activities. According to Assauri (2008:176) Inventory control is one of the activities of the activities sequence that are closely related to each other in the entire company's production operations in accordance with what has been planned both time, quantity, quality, and cost. In an effort to control inventory one of the methods that can be used is the